Protein kinases in neurodegenerative diseases: current understandings and implications for drug discovery - Xiaolei Wu; Zhangzhong Yang; Jinjun Zou; Huile Gao; Zhenhua Shao; Chuanzhou Li; Peng Lei (Signal Transduction and Targeted Therapy)
Abstract Neurodegenerative diseases (e.g., Alzheimer’s, Parkinson’s, Huntington’s disease, and Amyotrophic Lateral Sclerosis) are major health threats for the aging population and their prevalences continue to rise with the increasing of life expectancy. Although progress has been made, there is still a lack of effective cures to date, and an in-depth understanding of the molecular and cellular mechanisms of these neurodegenerative diseases is imperative for drug development. Protein phosphorylation, regulated by protein kinases and protein phosphatases, participates in most cellular events, whereas aberrant phosphorylation manifests as a main cause of diseases. As evidenced by pharmacological and pathological studies, protein kinases are proven to be promising therapeutic targets for various diseases, such as cancers, central nervous system disorders, and cardiovascular diseases. The mechanisms of protein phosphatases in pathophysiology have been extensively reviewed, but a systematic summary of the role of protein kinases in the nervous system is lacking. Here, we focus on the involvement of protein kinases in neurodegenerative diseases, by summarizing the current knowledge on the major kinases and related regulatory signal transduction pathways implicated in diseases. We further discuss the role and complexity of kinase–kinase networks in the pathogenesis of neurodegenerative diseases, illustrate the advances of clinical applications of protein kinase inhibitors or novel kinase-targeted therapeutic strategies (such as antisense oligonucleotides and gene therapy) for effective prevention and early intervention.